Nursing of a patient with dry eye caused by mites treated by thunder fire moxibustion combined with atomized fumigation of Traditional Chinese Medicine (眼部雷火灸联合中医雾化熏蒸治疗1例螨虫性干眼患者的护理体会) - WU Zeju (吴泽菊); YANG Jianying (杨剑英); WU Ningling (吴宁玲); HUANG Shaolan (黄少兰) (中西医结合护理)
This article summarizes the nursing measures for a patient with dry eyes caused by mites treated by eye thunder fire moxibustion combined with Traditional Chinese Medicine(TCM) atomization fumigation. Key issues of nursing included eye moxibustion, TCM atomization fumigation, meibomian gland massage, TCM scrubbing and routine life, medication, diet and emotional care. Eye thunder fire moxibustion combined with TCM atomization fumigation can achieve the effect of removing insects and soft fat, generating fluid and moistening dryness. Through dialectical nursing and targeted nursing intervention, It plays an active role in relieving clinical symptoms and promoting disease recovery. (本文总结了1例眼部雷火灸联合中医雾化熏蒸治疗螨虫性干眼患者的护理经验, 通过开展眼部雷火灸疗法、中药雾化熏蒸、睑板腺按摩、中药擦洗及常规的生活、用药、饮食和情志护理干预, 达到驱虫软脂, 生津润燥的作用, 有效地改善了患者的干眼症状。)